2011
DOI: 10.1029/2010jd015581
|View full text |Cite
|
Sign up to set email alerts
|

Gigantic jets produced by an isolated tropical thunderstorm near Réunion Island

Abstract: [1] Five gigantic jets (GJs) have been recorded with video and photograph cameras on 7 March 2010 above an isolated tropical storm east of Réunion Island. Three of them were produced before the storm reached its coldest cloud top temperature (approximately −81°C), and two others occurred during the cloud extension. Thanks to the close distance of observation (∼50 km), the luminosity within the cloud was recorded, and the events are analyzed in unprecedented detail. The tops of the GJs are estimated between 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
117
5
6

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(147 citation statements)
references
References 36 publications
19
117
5
6
Order By: Relevance
“…Even so, +CG flash rate was still much lower than that of Van der Velde et al [19]. Results in Soula et al [22] showed that no CGs occurred in tens of seconds before the GJ, and they suspected that the GJ was caused by intracloud lightning, in agreement with results obtained by Krehbiel et al [28], which was published in Nature. Further analysis on lightning location network data shows that 25 negative CGs occurred in 20 seconds before the GJ.…”
Section: Characteristics Of Lightning Activity In Gj-producing and Spsupporting
confidence: 80%
See 3 more Smart Citations
“…Even so, +CG flash rate was still much lower than that of Van der Velde et al [19]. Results in Soula et al [22] showed that no CGs occurred in tens of seconds before the GJ, and they suspected that the GJ was caused by intracloud lightning, in agreement with results obtained by Krehbiel et al [28], which was published in Nature. Further analysis on lightning location network data shows that 25 negative CGs occurred in 20 seconds before the GJ.…”
Section: Characteristics Of Lightning Activity In Gj-producing and Spsupporting
confidence: 80%
“…Three of the five gigantic jets occurred before the storm reached its coldest cloud top temperature (-81°C) and the other two occurred during the cloud extension. The extremely low frequency (ELF) data showed that the five gigantic jets reported by Soula et al [22] were also negative discharges.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies indicated that these events might be exclusively maritime [Su et al, 2003]. While this is no longer the case, jet events do appear to have a predilection for tropical disturbances [e.g., Cummer et al, 2009;Soula et al, 2011;Lu et al, 2011;Huang et al, 2012] and oceanic convection in general [van der Velde et al, 2010]. In contrast to jets, there is no direct evidence of a conductive current path to the cloud top below sprites, elves, or halos.…”
Section: Introductionmentioning
confidence: 83%